Biochemical composition and calorific content of fishes and shellfishes from Rushikulya estuary, south Orissa coast of India - Das, Snehalata; Sahu, B K (Indian Journal of Fisheries, 2011)
Biochemical composition of gonad, liver and muscle tissues of some importantcommercial fishes and shellfishes from Rushikulya estuary were analysed forlipid, carbohydrate, protein and calorific values. Protein content was found to bemore compared to carbohydrate and lipid in different organs of the fishes andshellfishes studied. Shellfishes were more proteinaceous than the other fishesinvestigated. Amongst the organs, gonad was protein and lipid dominant becauseof pre-spawning stage of maturation while liver was carbohydrate dominant inall the animals studied. The order of calorific values in fish and shellfish werenoticed to be gonad > liver > muscle. Penaeus monodon exhibited high calorificcontent compared to other organisms.